Ticlopidine Selectively Inhibits Human Platelet Responses to Adenosine Diphosphate - Cattaneo, Marco; Akkawat, Benjaporn; Lecchi, Anna; Cimminiello, Claudio; Capitanio, Anna M; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1991)
Platelet aggregation and fibrinogen binding were studied in 15 individuals before and 7 days after the oral administration of ticlopidine (250 mg b.i.d.). Ticlopidine significantly inhibited platelet aggregation induced by adenosine diphosphate (ADP), the endoperoxide analogue U46619, collagen or low concentrations of thrombin, but did not inhibit platelet aggregation induced by epinephrine or high concentrations of thrombin. Ticlopidine inhibited 125I-fibrinogen binding induced by ADP, U46619 or thrombin (1 U/ml). The ADP scavengers apyrase or CP/CPK, added in vitro to platelet suspensions obtained before ticlopidine, caused the same pattern of aggregation and 125I-fibrihogen binding inhibition as did ticlopidine. Ticlopidine did not inhibit further platelet aggregation and 125I-fibrinogen binding induced in the presence of ADP scavengers. After ticlopidine administration, thrombin or U46619, but not ADP, increased the binding rate of the anti-GPIIb/IIIa monoclonal antibody 7E3 to platelets. Ticlopidine inhibited clot retraction induced by reptilase plus ADP, but not that induced by thrombin or by reptilase plus epinephrine, and prevented the inhibitory effect of ADP, but not that of epinephrine, on the PGE1-induced increase in platelet cyclic AMP. The number of high- and low-affinity binding sites for 3H-ADP on formalin-fixed platelets and their Kd were not modified by ticlopidine. These findings indicate that ticlopidine selectively inhibits platelet responses to ADP.